2000
DOI: 10.1053/eupc.1999.0082
|View full text |Cite
|
Sign up to set email alerts
|

Does the mechanism of action of biatrial pacing for atrial fibrillation involve changes in cardiac haemodynamics? Assessment by Doppler echocardiography and natriuretic peptide measurements

Abstract: Acute BI pacing shortens the P-R interval and causes earlier left atrial contraction in relation to the surface electrocardiogram P wave. It does not alter the atrioventricular timing cycle, any other Doppler measurements or change cardiac peptide levels. This suggests that BI pacing does not cause haemodynamic changes that could account for any antifibrillatory properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
16
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 31 publications
4
16
0
Order By: Relevance
“…It is thought that the left atrial filling wave is interrupted by the left ventricular contraction in patients with normal AV conduction and prolonged intra-atrial conduction delay during RAA pacing, so we guessed that cardiac function would be markedly improved by BiA pacing compared with RAA pacing. Levy et al reported that BiA pacing made both left atrial and ventricular activation earlier, with no change in the left AV timing sequence, 12 but we demonstrated that the left side AV interval was shortened by RAA pacing. Dobrowska-Kugacka et al 13 also reported that the atrial hemodynamics during BiA pacing were not superior to those during RAA pacing and they also reported that pulmonary venous return could be reduced or left atrial pressure could be increased by BiA pacing.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…It is thought that the left atrial filling wave is interrupted by the left ventricular contraction in patients with normal AV conduction and prolonged intra-atrial conduction delay during RAA pacing, so we guessed that cardiac function would be markedly improved by BiA pacing compared with RAA pacing. Levy et al reported that BiA pacing made both left atrial and ventricular activation earlier, with no change in the left AV timing sequence, 12 but we demonstrated that the left side AV interval was shortened by RAA pacing. Dobrowska-Kugacka et al 13 also reported that the atrial hemodynamics during BiA pacing were not superior to those during RAA pacing and they also reported that pulmonary venous return could be reduced or left atrial pressure could be increased by BiA pacing.…”
Section: Discussionmentioning
confidence: 66%
“…14 They used a temporary DDD pacing mode, with 100 ms or 150 ms AV delay and without antiarrhythmic agents. We used AAI pacing or DDD pacing with optimal AV delay using an implanted pacemaker and antiarrhythmic agents and we consider that our study achieved a significant clinical result because the P wave duration during sinus rhythm was larger than in the 3 previous studies [12][13][14] and the intra-atrial conduction delay was prolonged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Levy et al (11) studied the hemodynamic effects in only eight patients with overdrive single chamber atrial pacing by transthoracic echocardiography. They showed that BiA pacing significantly decreased the interval from the atrial pacing spike on the ECG to the peak of the A-wave, but that there were no significant changes in A Vmax, TVI, plasma atrial natriuretic peptide, and B-type natriuretic peptide.…”
Section: Discussionmentioning
confidence: 99%
“…There are, however, few reports on the hemodynamic effects of BiA pacing, and the results that exist are controversial (11,12). We hypothesized that simultaneous and early activation of both atria by BiA pacing could improve atrial pressure and cardiac hemodynamics variables.…”
mentioning
confidence: 98%